Higher prevalence of obesity in Greek children living in rural areas despite increased levels of physical activity. Issue 9 (3rd June 2013) - Tambalis, Konstantinos D; Panagiotakos, Demosthenes B; Kavouras, Stavros A; Papoutsakis, Sofia; Sidossis, Labros S
Abstract : Aim: The purpose of the present study was to evaluate whether levels of physical activity (PA) and sedentary behaviours could explain observed differences in the prevalence of childhood obesity in a sample of Greek children. Methods: Epidemiological study. PA and sedentary behaviours were assessed by a self‐administrated PA checklist. Body mass index (BMI) was calculated from measured weight and height. A representative sample of Greek children aged 10–12 years attending fifth and sixth grade ( n = 3195), living in rural and urban areas, were enrolled. Maturation status was not evaluated due to technical reasons. Results: Prevalence of obesity was higher among children living in rural areas as compared with urban areas (12.1% vs. 10.7%, P < 0.01). Surprisingly, children living in rural areas had higher levels of self‐reported PA ( P < 0.001) and met current PA guidelines to a greater extent than their urban counterparts ( P < 0.05). Furthermore, boys had higher levels of total, low‐to‐moderate intensity and vigorous intensity physical activity, as well as sedentary behaviours, than girls (all P ‐values <0.05). Stratified analysis by BMI category revealed that normal weight boys and girls had higher levels of total PA and vigorous intensity physical activity compared with overweight and obese boys from the same type of setting (all P ‐values <0.05). Conclusions: Children living in rural areas have higher levels of PA and more frequently met PA guidelines than their urban counterparts, despite a higher prevalence of obesity.